Feasibility of Facial Nerve Preservation in Locally Advanced Parotid Squamous Cell Carcinoma Following Extended Neoadjuvant Chemotherapy: A Case Report - Janris Sitompul; I Gde Ardika Nuaba; I Dewa Gede Arta Eka Putra; I Wayan Sucipta; I Putu Santhi Dewantara (HM Publisher, 2026)
Background: Primary squamous cell carcinoma (SCC) of the parotid gland is a rare, aggressive malignancy often requiring radical parotidectomy with facial nerve sacrifice, particularly in T4b stage disease. The utility of neoadjuvant chemotherapy (NACT) in downstaging these tumors to facilitate functional nerve preservation remains controversial and under-reported in the literature. Case presentation: A 58-year-old male presented with a fixed, rapidly enlarging left preauricular mass classified as cT4bN2M0 (Stage IVA). The tumor involved the sternocleidomastoid muscle and encased the external carotid artery. Following a multidisciplinary tumor board decision, the patient underwent an extended course of six cycles of Paclitaxel and Carboplatin. The tumor exhibited a partial clinical response and significant central necrosis on imaging. Subsequently, a total parotidectomy was performed. Despite intraoperative fragility and adherence to deep vascular structures, the main trunk and primary divisions of the facial nerve were anatomically and functionally preserved. Histopathology confirmed high-grade SCC with perineural invasion limited to the distal excised branches, achieving clear margins. The patient received 66 Gy of adjuvant radiotherapy. At the 18-month follow-up, the patient remains disease-free with House-Brackmann Grade I facial function. Conclusion: Long-term facial nerve preservation is feasible in selected cases of locally advanced parotid SCC using a multimodal approach. Extended NACT may induce tumor necrosis and facilitate dissection along the neuro-vascular interface, provided that perineural invasion does not involve the main nerve trunk.